A long-overdue resource to tackle racism. (24th November 2022) - Foster, Sam
Abstract : Sam Foster, Chief Nurse, Oxford University Hospitals, discusses ethnic inequalities among patient groups and the NHS workforce and a resource to raise awareness and help combat racism